The development learning model of flipped classroom with digital storytelling for department of computer education - Srichailard, Panuwat (Kasetsart Journal of Social Sciences, 2023)
The objectives of the study were to: (1) Develop and study the efficiency a flipped classroom learning model with online digital storytelling for the department of computer education; (2) Compare the learning achievement of the learners before and after learning with the developed learning style; and (3) Study the satisfaction of the learners after learning with a flipped classroom learning model with an online digital storytelling method developed with the tools used in the research, including: (1) Classroom learning model is flipped with an online digital storytelling method evaluated by 10 experts; (2) Learning support system according to the developed learning model; (3) Management plan of flipped classroom with digital storytelling; (4) System quality assessment form; (5) Learning achievement test; and (6) System user satisfaction assessment form. The samples used in this research were 26 computer studies students from the faculty of science and technology Nakhon Pathom Rajabhat University. The data were analyzed by using mean, standard deviation, and t-test statistics. The results of the research found that: (1) The flipped classroom learning model with online digital storytelling was rated by expert assessment as most appropriate, The developed learning model had an efficiency of 87.69/80.26, which was higher than the benchmark set at 80/80; (2) The learners had higher learning achievement after studying than before studying. The learners had significantly higher after school achievement than before at .05 level; and (3) After studying with the classroom learning model, flipped classroom with online digital storytelling, the students’ satisfaction was at the highest level of satisfaction.